Linear-quadratic control problem with robust Quadratically constraints1 - T. Mouktonglang (2018)
We consider a problem of checking feasibility of linear quadratic control problem with robust quadratically constrained. The interior point method using NT-direction is proposed. The problem of finding descent direction is reduced to solve linear quadratic control problems with a linear term.